1987
DOI: 10.1007/bf00310059
|View full text |Cite
|
Sign up to set email alerts
|

Involution of the antimesometrial decidua in the mouse

Abstract: Involution of the antimesometrial decidua was analysed by electron microscopy on days 9, 10 and 11 of pregnancy in the mouse. During this period, the width of the antimesometrial decidua decreases considerably. Involution begins in the decidual cells situated closest to the embryo (internal decidua) and proceeds towards the myometrium. The cells of the internal decidua showed signs of deterioration characterized by accumulation of clumps of chromatin in the nuclei and dilation of the perinuclear cisterna and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
4

Year Published

1989
1989
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 14 publications
1
27
0
4
Order By: Relevance
“…ers, 1985Parr and Parr, 1989) may have accounted for the decline i n 5'-NT activity and mRNA between day 6 and day 9 of gestation. Lack of 5'-NT expression in the corresponding secondary decidua was supported by Northern blot analysis of the day 9 antimesometrium, an enriched source of secondary decidual cells (Krehbiel, 1937;Stewart and Peel, 1978;Katz and Abrahamsohn, 1987). An interesting pattern thus emerges for the relative distribution of 5'-NT, a n en-zyme which generates adenosine, and ADA which degrades adenosine.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…ers, 1985Parr and Parr, 1989) may have accounted for the decline i n 5'-NT activity and mRNA between day 6 and day 9 of gestation. Lack of 5'-NT expression in the corresponding secondary decidua was supported by Northern blot analysis of the day 9 antimesometrium, an enriched source of secondary decidual cells (Krehbiel, 1937;Stewart and Peel, 1978;Katz and Abrahamsohn, 1987). An interesting pattern thus emerges for the relative distribution of 5'-NT, a n en-zyme which generates adenosine, and ADA which degrades adenosine.…”
Section: Discussionmentioning
confidence: 89%
“…One developmental process likely to contribute such high levels of extracellular AMP is cell death (Pearson and Gordon, 1979;Gordon, 1986;Papadimitriou et al, 1991). This process has been described in the uterine epithelium (El-Shershaby and Hinchliffe, 1975;Parr and Parr, 1987), primary decidua (Welsh and Enders, 1987;Parr and Parr, 19891, and secondary decidua (Welsh and Enders, 1985;Katz and Abrahamsohn, 1987) during implantation chamber morphogenesis in rodents. Adenosine production by 5'-NT would, by this model, accompany the progression of cell death a t the uterine-embryo interface.…”
Section: Transmural Asymmetry Of Adenosine Concentration Across the Amentioning
confidence: 93%
“…104 Examination by electron microscopy showed that deteriorating decidual cells were apparently engaged in autolytic activity and that their elimination was facilitated by trophoblastic phagocytosis. 102 Instances of decidual cells being sloughed into the rat uterine lumen were also reported. 104 Chromatin degradation in the anti-mesometrial region in pregnant mice was recently confirmed by TUNEL staining.…”
Section: Cell Death In the Uterine Deciduamentioning
confidence: 98%
“…101 Involution then progresses towards the periphery as the number of dying cells (nuclear chromatin aggregation and mitochondrial distension) increases. 102 In the rat, cell degeneration also appears in the area immediately adjacent to the embryo 103 and then spread throughout the anti-mesometrial zone. 104 Examination by electron microscopy showed that deteriorating decidual cells were apparently engaged in autolytic activity and that their elimination was facilitated by trophoblastic phagocytosis.…”
Section: Cell Death In the Uterine Deciduamentioning
confidence: 99%
“…Acredita-se que a fagocitose facilite o processo de invasão embrionária, contribua com a nutrição inicial do embrião antes da formação da placenta e participe da aquisição de espaço para o desenvolvimento embrionário (Chhabra et al, 2012;Senner e Hemberger, 2010;Moffet-King 2002;Katz, Abrahamsohn, 1987;Kanaiazuma et al, 1984;Tachi et al, 1970).…”
Section: Introductionunclassified